TOLERANSI BERAGAMA SEBUAH KENISCAYAAN BAGI MUSLIM DALAM HIDUP BERMASYARAKAT - Pangeran, Ismail (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 13 No 1 (2017), 2017)
Indonesia is a nation that has various religions. Therefore, tolerance is essential to build a harmonious society. However, tolerance is not about faith, but social encounters. Cultural and religious differences must be an inspiration in building a nation to continue the ideals of the the founding fathers of this nation. Pancasila, Bhineka Tunggal Ika, NKRI, the 1945 Constitution is a fixed price that cannot be changed because it is the result of the agreement of the entire Indonesian people that must be maintained. To ensure the continuity of the Indonesian nation, the awareness of all religious people is needed to maintain it, because each religion teaches brotherhood, cooperation, affection, and tolerance in life. The difference is law of nature ( sunnatullah ) as evidence of the power of God, not leading into a conflict